2014
DOI: 10.14218/jcth.2014.00031
|View full text |Cite
|
Sign up to set email alerts
|

Thrombosis Associated with Viral Hepatitis

Abstract: Viral hepatitis may promote the development of venous thromboembolism (VTE) and, more specifically, portal vein thrombosis (PVT). In this narrative review, we summarize the clinical data and discuss the possible pathogenetic roles of cytomegalovirus (CMV), Epstein-Barr virus (EBV), and hepatitis A, B, and C viruses (HAV, HBV, HCV) in the occurrence of VTE. CMV is the first qualified candidate to enter the list of VTE minor risk factors, and in the rare case of fulminant infection, both EBV and CMV, like any se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 74 publications
0
28
0
Order By: Relevance
“…Keeping all of the above in mind, the combination of CMV viremia and CMV hepatitis likely contributed to the procoagulant state, leading to PVT. [ 29 , 32 ] These features likely also contributed to the prolonged debilitating fatigue prodrome, which was a unique feature in this case, as it suggested a prolonged failure to clear the virus, despite the patient's immunocompetent status. Although our patient did not require antiviral therapy, further study into the possible benefits of such therapy in cases with immunocompetent patients is warranted.…”
Section: Discussionmentioning
confidence: 91%
“…Keeping all of the above in mind, the combination of CMV viremia and CMV hepatitis likely contributed to the procoagulant state, leading to PVT. [ 29 , 32 ] These features likely also contributed to the prolonged debilitating fatigue prodrome, which was a unique feature in this case, as it suggested a prolonged failure to clear the virus, despite the patient's immunocompetent status. Although our patient did not require antiviral therapy, further study into the possible benefits of such therapy in cases with immunocompetent patients is warranted.…”
Section: Discussionmentioning
confidence: 91%
“…These findings agreed well with previous studies, which demonstrated that viral hepatitis might promote the development of venous thromboembolism. 22 , 23 The imbalance between procoagulant and anticoagulant factors associated with chronic liver disease might have clinical implications. 22 Moreover, RVO described in chronic hepatitis C was usually attributed to the treatment with interferon.…”
Section: Discussionmentioning
confidence: 99%
“… 22 , 23 The imbalance between procoagulant and anticoagulant factors associated with chronic liver disease might have clinical implications. 22 Moreover, RVO described in chronic hepatitis C was usually attributed to the treatment with interferon. 24 It seemed probable that a combination of active hepatitis C virus infection in a genetically susceptible individual receiving interferon accounted for the RVO.…”
Section: Discussionmentioning
confidence: 99%
“…Viral infections, such as hepatitis B are often associated with vasculitis and subsequently thromboembolic complications 7, 8, 34 . We therefore used immunoprecipitates isolated from a patient with ongoing hepatitis B infection and associated systemic vasculitis, to stimulate primary endothelial cells.…”
Section: Discussionmentioning
confidence: 99%